The impact of COVID-19 on low-emission dairy development in Kenya: Findings from a rapid scoping study - Odhong’, Charles; Wassie, Shimels Eshete; Dijk, Suzanne van; Wilkes, Andreas (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Key messages